Los factores de riesgo psicosocial y su incidencia en los accidentes de trabajo en el Cuerpo de Bomberos de Latacunga durante el año 2013. - Moreno Cruz, Robert Antonio (2015)
This study attempts to focus on issues that the Fire Department Staff has by studying some solutions to these issues. As a result of it, better work and professional standards were obtained. The threat to assess the psychosocial risks is due to a wide range of concepts, that is why it is essential to do an analysis and classification of psychological risks, as well as to check the different existing methods to evaluate them (Chapter II), generating a complete and methodical document which contains and represents all the information that authorities, security officers and other professionals who can lead in a comprehensible manner (Chapter IV). Finally, after doing the diagnostic process with the required information, was determined the source of risks. It will be presented the proposal to improve it (Chapter V), in which the general leadership can take decisions getting better the workers and employees’ health.